2000
DOI: 10.1177/073346480001900102
|View full text |Cite
|
Sign up to set email alerts
|

Psychotropic Drug Use and the Relation Between Social Support, Life Events, and Mental Health in the Elderly

Abstract: This study aimed to determine if self-reported social support and life events explained differences in levels of anxiety and depression among 109 elderly psychotropic drug users compared to 90 nonusers (aged 62 to 98). Two thirds of the respondents were French-speaking, mostly female (82.1%) and widowed (57.4%), and recipients of a home care program in Montreal, Canada. The life event and social support scales, broken down by item value, did not differentiate users from nonusers, except for feelings of lonelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Explaining cultural, ethnic, or racial disparities in use of health services is a complex endeavor, requiring analysis of predisposing, structural, access, and other variables in interaction [75-78]. In this review, two studies from Canada compared likelihood of use among French and English speakers, one finding an association with French speakers, albeit in a non-probability sample [79]. In addition, six studies from the United States compared the prevalence rate of psychotropic drug use between Whites and African-Americans.…”
Section: Resultsmentioning
confidence: 99%
“…Explaining cultural, ethnic, or racial disparities in use of health services is a complex endeavor, requiring analysis of predisposing, structural, access, and other variables in interaction [75-78]. In this review, two studies from Canada compared likelihood of use among French and English speakers, one finding an association with French speakers, albeit in a non-probability sample [79]. In addition, six studies from the United States compared the prevalence rate of psychotropic drug use between Whites and African-Americans.…”
Section: Resultsmentioning
confidence: 99%
“…As noted, BZDs tend to lose effectiveness as anxiolytics and sedatives after a few months of use. Also, long-term consumers may be more vulnerable to stressors (Pérodeau & Galbaud du Fort, 2000). Thus, invoking the use of BZDs to cope with future stress, like invoking multiple stressors, may be considered partly a justificatory strategy rather than an explanation, or, on the other hand, the pattern of BZD use would have the ironic effect of enhancing susceptibility to stress if not relieved by BZD consumption to cope with it.…”
Section: Use Of Benzodiazepines To Cope With Anticipated Stressorsmentioning
confidence: 94%
“…However, while such events can help to explain short-term consumption, they do not appear to predict long-term use (Ankri, Collin, Pérodeau, & Beaufils, 2002;. Furthermore, it has been shown that users of psychotropic drugs do not experience more stressful events than non-users (Pérodeau & Galbaud du Fort, 2000), although very few studies have explored this relationship. Hence stressors might be considered as justifications rather than explanations.…”
Section: Justification Of Use By Invoking Multiple Stressorsmentioning
confidence: 95%
“…In a sample of elderly home care recipients, prescription drug users felt psychologically more distressed than nonusers when experiencing comparable levels of solitude and frustration stemming from an unsatisfactory social life (Pérodeau & Galbaud du Fort, 2000). Poor mental health and prescription drug use among the elderly have been related to reported feelings of loneliness (Gustafsson, Isacson, Thorslund, & Sörbom, 1996) and perceived inadequate social ties and support (Allard, Allaire, Leclerc, & Langlois, 1995).…”
Section: Physical and Psychological Correlates Of Prolonged Usementioning
confidence: 99%